Populations genetics and the evolution of herbicide resistance in weeds - Jasieniuk, M.; Maxwell, B.D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Numerous factors, including mutation, selection, inheritance, mating System, and gene flow are important in the evolution of herbicide resistance in weeds. Spontaneous gene mutation is believed to be the main source of genetic variation for resistance evolution in a geographic region in which resistance has not been detected previously. Despite mutation frequencies that are probably very low, the probability of occurrence of at least a single resistant mutant in a susceptible population may be high for weed species with high fecundities and large population sizes. Subsequent repeated treatments with herbicides having the same mode of action could lead to the rapid evolution of predominantly resistant populations. Rare dominantly inherited resistance mutations spread significantly more rapidly than recessive mutations in random mating populations, but at roughly the same rate in highly self-fertilizing species. Gene flow, through the movement of pollen or seed from resistant weed populations, may provide a source of resistance alleles to adjacent or nearby susceptible fields. Mathematical models indicate that the strength of selection imposed by a herbicide and the initial frequency of the resistant phenotype most strongly influence the rate of resistance evolution. The models predict that the most effective strategies to manage resistance are to reduce the intensity of selection by herbicide and to limit the migration of herbicide-resistant seed.